Verification of K-step and infinite-step opacity of bounded labeled Petri nets. (June 2022) - Tong, Yin; Lan, Hao; Seatzu, Carla
Abstract: Opacity is an important information security property. Given a discrete event system, a set of secret states, and an intruder who observes the system evolution through an observation mask, the system is said to be K -step opaque if the intruder is not able to ascertain that the system is or was in a secret state at some time within K steps, namely within the observation of K events. If the intruder is never able to ascertain that the system is or was in a secret state at any time, the system is said to be infinite-step opaque. This work aims at verifying the two opacity properties when the discrete event system is modeled as a bounded labeled Petri net. Using the notion of basis reachability graph, new approaches are proposed to check K -step opacity and infinite-step opacity. The proposed approaches are shown to be more efficient than the standard methods based on the reachability graph.